2019
DOI: 10.21147/j.issn.1000-9604.2019.04.11
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of COC183B2 antibody targeting ovarian cancer by near-infrared fluorescence imaging

Abstract: ObjectiveTo evaluate the imaging potential of a novel near-infrared (NIR) probe conjugated to COC183B2 monoclonal antibodies (MAb) in ovarian cancer (OC).MethodsThe expression of OC183B2 antigen in OC was determined by immunohistochemical (IHC) staining using tissue microarrays with the H-score system and immunofluorescence (IF) staining of tumor cell lines. Imaging probes with the NIR fluorescent dye cyanine 7 (Cy7) conjugated to COC183B2 Mab were chemically engineered. OC183B2-positive human OC cells (SKOV3-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…However, antibodies conjugated with USPIOs might be toxic. Cy7 has not been approved for use in humans, and our previous work showed the phenomenon of lung accumulation of Cy7-conjugated COC183B2 [10]. As previously described, IRDye800CW is a safe and effective NIRF dye.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…However, antibodies conjugated with USPIOs might be toxic. Cy7 has not been approved for use in humans, and our previous work showed the phenomenon of lung accumulation of Cy7-conjugated COC183B2 [10]. As previously described, IRDye800CW is a safe and effective NIRF dye.…”
Section: Discussionmentioning
confidence: 73%
“…Moreover, the lesions of patients are not visible during the operation due to the imaging modality. We later conjugated ultrasmall superparamagnetic iron oxide nanoparticles (USPIOs) and Cy7 with COC183B2 antibody and achieved early detection of EOC through OC183B2targeted MRI and fluorescence imaging [10,25]. However, antibodies conjugated with USPIOs might be toxic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of note, it has repeatedly been suggested that patients responding immunologically to DC therapy have better outcomes. [12][13][14][15] This finding could indicate that immune competent patients have better outcomes than highly immune suppressed patients, [16][17][18] without DCs necessarily playing a role. An interesting outlier to lack of randomized efficacy is sipuleucel T, which is a mixed product containing T cells and DCs.…”
Section: Introductionmentioning
confidence: 99%
“…We proved the tumor-specific imaging ability of COC183B2-Cy7 in tumor tissue from a mouse model. 16 However, it remains unclear whether COC183B2-Cy7 can detect metastatic lymph nodes, and its specific in vivo biodistribution and ability to identify tiny metastatic lesions remain unknown. Therefore, we aimed to detect OC183B2 expression in metastatic lymph nodes and to determine the imaging parameters of COC183B2-Cy7 in a mouse subcutaneous tumor model.…”
mentioning
confidence: 99%